Inappropriate use of ritodrine hydrochloride for threatened preterm birth in Japan: a retrospective cohort study using a national inpatient database - Daisuke Shigemi; Shotaro Aso; Hideo Yasunaga (BMC, 2019)
Abstract Background No study has revealed the effectiveness of long-term tocolysis for patients diagnosed with threatened preterm birth, and the use of betamimetics in these patients has not been recommended in the United States or Europe because of the potential for severe maternal adverse effects. However, long-term tocolysis with intravenous infusion of ritodrine hydrochloride, a betamimetic, can be selected as the first-line tocolytic treatment in Japan. This study was performed to (i) examine the current status of long-term tocolytic treatment, particularly with intravenous infusion of betamimetics, for threatened preterm birth in Japan and (ii) clarify the association between long-term tocolytic treatment and maternal adverse effects. Methods This retrospective cohort study was conducted using a national inpatient database for acute-care inpatients in Japan. Among all pregnant women who were diagnosed with threatened preterm birth and admitted to the hospital from July 2010 to March 2016, we identified 134,959 eligible patients. The primary outcome was maternal serious adverse effects during hospitalization. A multivariable logistic regression analysis was performed to evaluate factors associated with maternal adverse effects. Results Among all patients, 17.2% received intravenous infusion of ritodrine hydrochloride for ≤48 h and 28.7% received this treatment for ≥28 days. The proportion of maternal adverse effects was significantly higher among patients treated for ≥28 days than ≤48 h. A longer duration of tocolysis was significantly associated with increased maternal adverse effects. Conclusions Long-term tocolysis was associated with an increased incidence of maternal adverse effects in the current study using real-world data. Japanese clinicians should adjust their tocolytic treatment practices in accordance with the latest scientific evidence or make efforts to verify the effectiveness and safety of long-term tocolysis.